Pusa hispida Schreber 1775 - Wilson, Don E.; Reeder, DeeAnn (The Johns Hopkins University Press, 2005)
Pusa hispida Schreber 1775 Pusa hispida Schreber 1775, Die Saugethiere, Vol. 2, 13: pl. 86 [1775]; see also text 3 (17): 312 [1776]. Type Locality: "Man fängt ihn auf den Küsten von Grönland und Labrader". Vernacular Names: Ringed Seal. Subspecies:: Subspecies Pusa hispida subsp. hispida Schreber 1775 Subspecies Pusa hispida subsp. botnica Gmelin 1788 Subspecies Pusa hispida subsp. ladogensis Nordquiest 1899 Subspecies Pusa hispida subsp. ochotensis Pallas 1811 Subspecies Pusa hispida subsp. saimensis Nordquist 1899 Distribution: Arctic Ocean and coastal regions of Açôres (vagrant), Canada (Nettilling Lake, Baffin Isl), China (vagrant: Jiangsu), Estonia, Finland (Saimaa Lake), Germany (vagrant), Greenland, Japan (Hokkaido, vagrant: Shikoku, Kyushu), Latvia, Lithuania, Norway, Portugal (vagrant), Russia (Okhotsk, Bering, and Baltic Seas), Sweden, USA (vagrant: New Jersey, California). Conservation: U.S. ESA – Endangered as Phoca hispida saimensis IUCN – Endangered as P. h. saimensis , Vulnerable as P. h. botnica and P. h. ladogensis , Lower Risk as P. hispida and as P. h. ochotensis . Discussion: Placed in Pusa Scopoli, 1771, by Scheffer (1958) and Rice (1998). Mohr (1952) described successful mating in captivity between Pusa hispida and Halichoerus grypus . Published as part of Wilson, Don E. & Reeder, DeeAnn, 2005, Order Carnivora, pp. 532-628 in Mammal Species of the World: a Taxonomic and Geographic Reference (3 rd Edition), Volume 1, Baltimore :The Johns Hopkins University Press on page 600, DOI: 10.5281/zenodo.7316519